2019
DOI: 10.1111/ejn.14388
|View full text |Cite
|
Sign up to set email alerts
|

From clock to functional pacemaker

Abstract: In mammals, the central pacemaker that coordinates 24‐hr rhythms is located in the suprachiasmatic nucleus (SCN). Individual neurons of the SCN have a molecular basis for rhythm generation and hence, they function as cell autonomous oscillators. Communication and synchronization among these neurons are crucial for obtaining a coherent rhythm at the population level, that can serve as a pace making signal for brain and body. Hence, the ability of single SCN neurons to produce circadian rhythms is equally import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 117 publications
(133 reference statements)
0
45
0
Order By: Relevance
“…Specifically, the properties that turn a community of individual cell oscillators into a coherent and reliable circadian pacemaker originate from the SCN itself [56,57]. The comparison of individual SCN neuron electrical rhythmicity in dispersed cell cultures and within SCN slices revealed that circadian precision increases significantly when the native tissue context is preserved.…”
Section: The Origin Of Circadian Precision and Robustness Within Tmentioning
confidence: 99%
“…Specifically, the properties that turn a community of individual cell oscillators into a coherent and reliable circadian pacemaker originate from the SCN itself [56,57]. The comparison of individual SCN neuron electrical rhythmicity in dispersed cell cultures and within SCN slices revealed that circadian precision increases significantly when the native tissue context is preserved.…”
Section: The Origin Of Circadian Precision and Robustness Within Tmentioning
confidence: 99%
“…Pacemaker cells function individually as autonomous single-cell oscillators and together, as an ensemble, in a highly synchronized way as a multioscillator system. Multioscillator systems in the suprachiasmatic nucleus control circadian rhythms in the brain and other individual organs (Michel and Meijer 2020). The oscillation at the single pacemaker cell level is based on a negative feedback loop wherein the level of clock gene expression is determined by the amount of the corresponding protein product accumulated within the cell (Buhr and Takahashi 2013).…”
Section: Pacemaker Cellsmentioning
confidence: 99%
“…If single-cell oscillations of pacemaker cells in the suprachiasmatic nucleus run uncoordinated or in different phases, the multioscillator system is desynchronized, and, in consequence, the brain and other organs function with different circadian rhythms. Thus, a unified circadian rhythm across the organism requires sufficient synchronization among pacemaker cells (Michel and Meijer 2020).…”
Section: Pacemaker Cellsmentioning
confidence: 99%
“…The authors point out that the fruit fly is a classic model that can be used to study the interactions between the circadian clock and age‐related decline because of the short life span and the neurogenetic tools that are available (De Nobrega & Lyons, ). In mammals, ageing impacts SCN‐regulated pathways, including sleep timing and entrainment to the LD cycle (Michel & Meijer, ). Specifically, electrical and neurochemical rhythms that are dampened in the aged SCN are due, at least in part, to an increase in firing of an anti‐phased SCN neuronal subpopulation.…”
Section: Evolution and Adaptation Of Clocksmentioning
confidence: 99%